2017
DOI: 10.5455/medarh.2017.71.341-346
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Quality of Life and Depression Among Persons Suffering from Psoriasis

Abstract: Introduction:Chronic dermatitis is a major sociomedical issue still being marginalized due to generally accepted view that skin diseases are less of a health problem than is the case with diseases of other organs and organ systems for they are not life-threatening. Measurement of quality of life of persons suffering from psoriasis could become an important factor in assessing the success of treatment and modern aspect of integration of the diseased into the planning of therapeutic procedures, monitoring of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Reduced general well-being and higher rates of depression have also been demonstrated in people without diabetes who had other chronic skin lesions, although very different methods and small samples were used for the assessment. Patients with atopic dermatitis have a similarly reduced quality of life [ 13 ], and patients suffering from psoriasis are more likely to suffer from depression when advanced disease is present [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced general well-being and higher rates of depression have also been demonstrated in people without diabetes who had other chronic skin lesions, although very different methods and small samples were used for the assessment. Patients with atopic dermatitis have a similarly reduced quality of life [ 13 ], and patients suffering from psoriasis are more likely to suffer from depression when advanced disease is present [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals without diabetes, rheumatological diseases [ 13 ] and chronic active skin diseases affect the quality of life [ 14 , 15 ]. To date, no studies of diabetic rheumatological manifestations or diabetic skin lesions have explored associations with quality of life in patients with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…A significantly negative correlation was found between this domain and the degree of depression (r s =-0.546 ** ) which suggests that the lower the quality of life the higher the rate of depression and vice versa. Mahmutovic et al (34) found a similar negative correlation in this domain (rho=-0.598 ** p = 0.0001). Therefore, the general public should be better informed about the disease in order to reduce stigmatization and improve the quality of life of the patients (14,20).…”
Section: Discussionmentioning
confidence: 55%
“…In spite of the significant prevalence and incurability of psoriasis, its relation to quality of life and psychological problems, such as depression and anxiety, has been analyzed in only a few studies [ 41 , 42 ]. Designing appropriate interventions to improve the psychological conditions of patients with psoriasis requires preliminary analyses of the effective and protective factors in this disease.…”
Section: Introductionmentioning
confidence: 99%